Observations on the Global Spread of Physician Assistant Education. (October 2017) - Ballweg, Ruth M.; Hooker, Roderick S.
Abstract : Abstract: The physician assistant concept was developed in the 1960s as a response to the shortage and uneven distribution of generalist doctors. The goal was to increase the public's access to health care. After a half century of development and implementation, the PA model has become a global strategy to augment medical service delivery. In many instances the introduction of the PA was successful. Elsewhere it is in the early stages of development. The name may be modified depending on the country: "physician associate, " "clinical assistant, " "associate physician" are alternatives. While not all PA start-ups have been successful, where the PA model is thriving and growing, the concept provides rich examples of adaptation and evolution. The notion of including a PA is based on the concept of a medical team model and modified depending on the needs of the nation's health structure, regulation, and policy. Along the way, the education process undergoes modification, depending on the needs of the nation, but what emerges is a strategy for augmenting a stretched physician cadre. The reasons for success and failure are multifactorial, and the early implementation of a PA program can be a daunting task. This article examines the PA education experience in 15 countries. Successful use of PAs suggests that flexible adaptation to health care demand, generalist education, physician acceptance, and cost-effectiveness analysis may be keys that influence policy and their retention. In the end, success, adaptation, and failures are the lessons learned.